Sustainable Maritime Supply Chain (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Moving toward a collaborative and cooperative maritime ecosystem has been a hot topic of discussion for a while, to the point that for maritime supply actors, co-innovation should now be the new normal. In order to manage the end-to-end integration of maritime supply chain processes, each stakeholder needs to control their maritime supply chain (i.e., reduce uncertainty) and create value (e.g., cost reduction) for every actor involved in the sustainable maritime ecosystem, with the aim of serving their customers better. Given this context, technological challenges (e.g., different standards, interoperability, cybersecurity, and energy consumption) must be faced from a logistic corridor point of view in order to guarantee the greatest advantages for all involved actors. A cooperative maritime system is a step toward creating a maritime supply chain ecosystem or network, but ad hoc initiatives should be replaced by more overarching strategies. Moving toward a collaborative and cooperative maritime sector is thus the next logical step for maritime supply chain actors in order to enable innovation and create a new competitive edge. From the industrial and economic perspectives, this trend of (maritime) actors banding together to form platform-enabled ecosystems can increase their strengths and competitiveness (Sys and Vanelslander, 2020). Thus, the implementation of a cooperative ecosystem is paramount in order to achieve the required sustainability goals.